Dynamic Response of Bridge Subjected to Eccentrically Moving Flexible Vehicle: A Semianalytical Approach - R. Lalthlamuana; S. Talukdar (Shock and Vibration)
Dynamic response of a single span bridge subjected to moving flexible vehicles has been studied using a semianalytical approach. The eccentricity of vehicle path giving rise to torsional motion of the bridge has been incorporated in the approach. The bridge surface irregularity has been considered as the nonhomogeneous process in spatial domain. A closed form expression has been derived to generate response samples corresponding to each input of roughness profile to form an ensemble. Thereafter, averaging across the ensemble has been carried out at each time step to determine mean and standard deviation of bridge and vehicle response. Further, dynamic amplification factor (DAF) of the bridge response has been obtained for several combinations of bridge-vehicle parameters. The study reveals that structural bending modes of vehicle can significantly reduce dynamic response of the bridge. The eccentricity of vehicle path and flexural/torsional rigidity ratios plays a significant role in dynamic amplification of bridge response.